2012
DOI: 10.1038/bjc.2012.271
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-guided surgical sampling of glioblastoma identifies phenotypically distinct tumour-initiating cell populations in the tumour mass and margin

Abstract: Background:Acquiring clinically annotated, spatially stratified tissue samples from human glioblastoma (GBM) is compromised by haemorrhage, brain shift and subjective identification of ‘normal' brain. We tested the use of 5-aminolevulinic acid (5-ALA) fluorescence to objective tissue sampling and to derive tumour-initiating cells (TICs) from mass and margin.Methods:The 5-ALA was administered to 30 GBM patients. Samples were taken from the non-fluorescent necrotic core, fluorescent tumour mass and non-fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 33 publications
2
89
1
1
Order By: Relevance
“…18 Higher levels of fluorescence have higher levels of ALA-induced protoporphyrin concentration and correlate strongly with increasing malignancy (histopathological score) and tissue proliferation. 2,31 To our knowledge, there are only 2 studies that have directly addressed the relationship of intraoperative ALA fluorescence intensity with degree of cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Higher levels of fluorescence have higher levels of ALA-induced protoporphyrin concentration and correlate strongly with increasing malignancy (histopathological score) and tissue proliferation. 2,31 To our knowledge, there are only 2 studies that have directly addressed the relationship of intraoperative ALA fluorescence intensity with degree of cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…However, few cellular and molecular analyses have been performed in this area. Some studies have shown that residual, unresected tumor cells display alterations different from those of cells isolated from the corresponding tumor mass [12][13][14]. A better understanding of the characteristics of the PBZ and tumor cell infiltration in this region is critical to unravel the mechanisms underlying the recurrence of GB and to optimize the quality of surgical resection and the development of new therapies.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is still possible that GBM CSCs co-localize with the tumor and hence are accessible for a local therapy. This is also suggested by Piccirillo et al 112 showing the presence of cells within the tumor margin permitting high engraftment rates in vivo, so these cells appear not to enable the self-renewal of a major identi¯er of cancer stem cells.…”
Section: Discussionmentioning
confidence: 50%